Perampasan Aset Tindak Pidana Pencucian Uang yang Tidak Berasal dari Hasil Tindak Pidana : Studi Putusan Mahkamah Agung RI No. 669K/Pid.Sus/2017 - Agusta Kanin; Madiasa Ablisar; Mahmud Mulyadi; Jelly Leviza (Universitas Sumatera Utara, 2019)
Abstract. In the practice of appropriation of assets of criminal acts through the anti-money laundering law instrument, there has been seizure of assets that have absolutely no assets in relation to the original crime and have also been proven by the defendant. This is stated in the Republic of Indonesia Supreme Court Decision No. 669K / PID.SUS / 2017 has confiscated the assets of the defendant who did not come from a predicate crime of narcotics. In addition, imposing a penalty on the defendant with imprisonment for 13 (thirteen) years and a fine of Rp. 10,000,000,000 (ten billion rupiah) of subsidies 1 (one) year in prison. The assets confiscated consisted of movable objects in the form of trucks and immovable objects in the form of waste processing plants. All of the defendant's assets were declared to have been seized for the state. This study tries to analyze how the legal effort that must be taken by the defendant in defending his assets that do not come from a criminal act. The interesting thing to be studied and analyzed is regarding the deprivation of assets resulting from narcotics crime, whether by criminal, civil or administrative. Furthermore, regarding the legal remedies taken by the convicted person to file legal remedies if there are assets that do not originate from narcotics crimes, the court's decision states that the assets were seized for the state. Keywords : deprivation of assets; money laundering crime; and the results of narcotics crime.